Social media use and entrepreneurial intention of students in higher education - Afranie, Jennifer; Afriyie, Emelia Ohene; Bans-Akutey, Anita; Opare Darko, Lawrencia Irene (Annals of Management and Organization Research, 2024)
Purpose: Social media use has become pervasive in the lives of students in both academic and nonacademic activities. This study aimed to assess the influence of social media use on the entrepreneurial intention of final-year students of the Higher National Diploma (HND) final year students of Accra Technical University (ATU). Research Methodology: The study used a descriptive research methodology that adopted a quantitative research approach; with a population of HND final-year students, data were gathered from 200 respondents through questionnaires. Purposive sampling was used to select participants for the study. The data received from the respondents were analyzed using descriptive and inferential statistics using IBM SPSS Statistics 24. Results: The results showed that students were very active on social media and found it very useful. Five-year students considered entrepreneurship a career choice after school.  The results also indicated that social media use had a significant direct effect on students’ entrepreneurial intention. Limitations: This study focused on social media use as a determinant of entrepreneurial intention, and was limited to final-year HND students. Contribution: Tertiary institutions, as part of entrepreneurship education, should allow students to explore the use of social media to advance the entrepreneurship drive as this increases entrepreneurial intention. Practical Implications: Educators must inculcate the use of social media in practical activities during entrepreneurship education. Future research should examine how specific social media sites contribute to improving entrepreneurial intention among final-year students in tertiary institutions. Novelty: This study examined social media as a factor influencing students’ entrepreneurial intentions.